Key steps in the morphogenesis of a cranial placode in an invertebrate chordate, the tunicate Ciona savignyi - Kourakis, Matthew J. (2010)
Tunicates and vertebrates share a common ancestor that possessed cranial neurogenic placodes, thickenings in embryonic head epidermis giving rise to sensory structures. Though orthology assignments between vertebrate and tunicate placodes are not entirely resolved, vertebrate otic placodes and tunicate atrial siphon primordia are thought to be homologous based on morphology and position, gene expression, and a common signaling requirement during induction. Here, we probe key points in the morphogenesis of the tunicate atrial siphon. We show that the siphon primordium arises within a non-dividing field of lateral-dorsal epidermis. The initial steps of atrial primordium invagination are similar to otic placode invagination, but a placode-derived vesicle is never observed as for the otic vesicle of vertebrates. Rather, confocal imaging reveals an atrial opening through juvenile stages and beyond. We inject a photoactivatable lineage tracer to show that the early atrial siphon of the metamorphic juvenile, including its aperture and lining, derives from cells of the atrial placode itself. Finally, we perturb the routing of the gut to the left atrium by laser ablation and pharmacology to show that this adaptation to a sessile lifestyle depends on left-right patterning mechanisms present in the free-swimming chordate ancestor.